Film, Theory and Philosophy : the Key Thinkers. - Colman, Felicity (Taylor and Francis, 2014)
Philosophy, and in particular continental philosophy, has provided a conceptual underpinning for cinema since its beginnings, especially in the development of cinematic aesthetics. In its turn, film has rethought the abstractions of space and time and the categories of sex and gender and has created new concepts which illuminate phenomenology, metaphysics and epistemology. ""Film and Philosophy"" brings together leading scholars to provide a detailed overview of the key thinkers who have shaped the field of film philosophy. The thinkers include continental and 'post-continental' philosophers,